Jízdárna - Poláček, Petr (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Bakalářská práce se zabývá návrhem nosné ocelové konstrukce jízdárny. Jízdní plocha má rozměry 25 x 60 m. Rozpětí příčné vazby je 36 m. Příčné vazby jsou od sebe vzdáleny 9 m. Hala je vysoká 10,5 m. Konstrukce je navržena pro oblast Svitávka u Letovic

Bachelor thesis with the disign of the steel load-bearing structure of riding hall. Trackway area has plan dimension of 25 x 60 m. Span of main frame is 36 m. Main frame are distanced 9 m. The hall is 10,5 m hight. The structure is design for the area of Svitávka near Letovice.
Riding hall
Keywords: jízdárna; ocelová konstrukce; dvoukloubový rám; příhradová příčel; vzpěrková vaznice; uzavřený ocelový profil; čepový spoj; trapézový plech; riding hall; steel structure; double joint main frame; trus; purlin with fly bracing; square hollow section; pin joint; trapezoidal sheet